2017
DOI: 10.1136/bcr-2016-217250
|View full text |Cite
|
Sign up to set email alerts
|

Bladder calculus leading to acute renal failure in a girl child: a rare cause

Abstract: A 10-year-old girl presented with acute renal failure (ARF) with a serum creatinine of 7.5 mg/dL. Imaging showed bilateral hydroureteronephrosis and a large bladder stone (75×55 mm). The large bladder stone was probably the aetiology of bilateral hydronephroureter and ARF as no other cause could be found. An open cystolithotomy was performed. Ten days after the surgery, serum creatinine decreased to 0.7 mg/dL. In this report, we highlight an unusual cause of renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…9,10 Komeya et al in 2013 found only six English literatures in which bladder stones were described to have caused renal failure in the last several decades. 10 Interestingly, most of the bladder stones in Komeya's review weighed between 200gm and 450gm with only one case weighing 1640gm. 11 Diniz et al who performed the literature review on giant bladder stone and renal failure a few years later, concluded that bladder stone greater than 400 grams may be associated with renal failure.…”
Section: Discussionmentioning
confidence: 98%
“…9,10 Komeya et al in 2013 found only six English literatures in which bladder stones were described to have caused renal failure in the last several decades. 10 Interestingly, most of the bladder stones in Komeya's review weighed between 200gm and 450gm with only one case weighing 1640gm. 11 Diniz et al who performed the literature review on giant bladder stone and renal failure a few years later, concluded that bladder stone greater than 400 grams may be associated with renal failure.…”
Section: Discussionmentioning
confidence: 98%
“…BUN and creatinine were also tested in this patient, but no increase was found. Kidney damage due to bladder stones has rarely been reported ( 18 ). Another complication is rectal prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…15 According to a study 7.4% cases operated with transurethral pneumatic lithotripsy require second surgery for stone fragments removal and prolonged hospital stay is required. 16 Laser or pneumatic and ultrasonic lithoclast combined method can be used for large urinary bladder stones but this technique is very costly and devices need proper care, highly expert person to use it so it is not suitable for small healthcare centers to afford it. 17,18 According to a study cystolithoclast method reported minor complications in 10% cases, postoperative hematuria developed in 05% cases which was settled after few hours and difficulty in urination was experienced by 04% cases and urinary retention was experienced by 01% cases which was relieved by passing urinary catheter.…”
Section: Discussionmentioning
confidence: 99%